The physics of multiphase gas flows: fragmentation of a radiatively cooling gas cloud in a hot wind. Issue 4 (10th November 2018) - Sparre, Martin; Pfrommer, Christoph; Vogelsberger, Mark
ABSTRACT: Galactic winds exhibit a multiphase structure that consists of hot-diffuse and cold-dense phases. Here we present high-resolution idealized simulations of the interaction of a hot supersonic wind with a cold cloud with the moving-mesh code arepo in setups with and without radiative cooling. We demonstrate that cooling causes clouds with sizes larger than the cooling length to fragment in 2D and 3D simulations. We confirm earlier 2D simulations by McCourt et al. (2018 ) and highlight differences of the shattering processes of 3D clouds that are exposed to a hot wind. The fragmentation process is quantified with a friends-of-friends analysis of shattered cloudlets and density power spectra. Those show that radiative cooling causes the power spectral index to gradually increase when the initial cloud radius is larger than the cooling length and with increasing time until the cloud is fully dissolved in the hot wind. A resolution of around 1 pc is required to reveal the effect of cooling-induced fragmentation of a 100 pc outflowing cloud. Thus, state-of-the-art cosmological zoom simulations of the circumgalactic medium fall short by orders of magnitudes from resolving this fragmentation process. This physics is, however, necessary to reliably model observed column densities and covering fractions of Lyman α haloes, high-velocity clouds, and broad-line regions of active galactic nuclei.